CD146+CAFs promote progression of endometrial cancer by inducing angiogenesis and vasculogenic mimicry via IL-10/JAK1/STAT3 pathway - Zhicheng Yu; Qian Zhang; Sitian Wei; Yang Zhang; Ting Zhou; Qi Zhang; Rui Shi; Dmitry Zinovkin; Zahidul Islam Pranjol; Jun Zhang; Hongbo Wang (Cell Communication and Signaling, 2024)
Abstract Heterogeneous cancer-associated fibroblasts (CAFs) play important roles in cancer progression. However, the specific biological functions and regulatory mechanisms involved in endometrial cancer have yet to be elucidated. We aimed to explore the potential mechanisms of heterogeneous CAFs in promoting endometrial cancer progression. The presence of melanoma cell adhesion molecule (MCAM; CD146) positive CAFs was confirmed by tissue multi-immunofluorescence (mIF), and fluorescence activated cell sorting (FACS). The biological functions were determined by wound healing assays, tuber formation assays and cord formation assays. The effects of CD146+CAFs on endometrial cancer cells were studied in vitro and in vivo. The expression level of interleukin 10 (IL-10) was measured by quantitative real time polymerase chain reaction (qRT-PCR), western boltting and enzyme linked immunosorbent assays (ELISAs). In addition, the transcription factor STAT3 was identified by bioinformatics methods and chromatin immunoprecipitation (ChIP). A subtype of CAFs marked with CD146 was found in endometrial cancer and correlated with poor prognosis. CD146+CAFs promoted angiogenesis and vasculogenic mimicry (VM) in vitro. A xenograft tumour model also showed that CD146+CAFs can facilitate tumour progression. The expression of IL-10 was elevated in CD146+CAFs. IL-10 promoted epithelial-endothelial transformation (EET) and further VM formation in endometrial cancer cells via the janus kinase 1/signal transducer and activator of transcription 3 (JAK1/STAT3) signalling pathway. This process could be blocked by the JAK1/STAT3 inhibitor niclosamide. Mechanically, STAT3 can bind to the promoter of cadherin5 (CDH5) to promote its transcription which may be stimulated by IL-10. We concluded that CD146+CAFs could promote angiogenesis and VM formation via the IL-10/JAK1/STAT3 signalling pathway. These findings may lead to the identification of potential targets for antiangiogenic therapeutic strategies for endometrial cancers.